Technical analysis of soil cement as a construction material applied in rural houses - Gamboa Tolentino, Erick Oswaldo (2022)
The project reveals the properties of soil cement as a construction material in rural houses. The context of this research was in Pilcomayo district, Huancayo, Peru, due to the high abundance of poor constructions without any security or comfort for the inhabitants of the area. In the experiment, the technical analysis of the soil cement was carried out with doses of 5%, 9%, 13%, 17% and 21% of cement, applying tests of Granulometry, Compaction, Compression and Durability established by the Portland Cement Association. It was found that the soil of the district has an efficient granulometry for the use of soil cement, and also that it has a resistance of 129.42 kg-f/cm2 with 21% cement at 28 days of curing. The lab test results also showed that the cement soil loses just 4.22% in weight with 17% of cement in the durability test, as well as with this same percentage. The soil cement presents a higher maximum compaction density of 2,255 g/cm3. These results propose alternative applications for soil cement according to their resistance, granulometry and durability. According to the Peruvian Technical Standard, the minimum f'c for floor concrete base is 100 kg/cm2, a dosage of 19% cement was proposed for this element, and for brick masonry the minimum f'c is 50kg/cm2, so it was proposed 12% cement to meet this requirement, in addition, the soil cement was proposed as a slope protection with 17% cement since it achieved good results in the durability test. Keywords Soil Cement, Resistance, Comfort, Dosing, Durability